Randomized Controlled Clinical Trial of Fractional Doses of Inactivated Poliovirus Vaccine Administered Intradermally by Needle-Free Device in Cuba - Resik, Sonia; Tejeda, Alina; Mas Lago, Pedro; Diaz, Manuel; Carmenates, Ania; Sarmiento, Luis; Alemañi, Nilda; Galindo, Belkis; Burton, Anthony; Friede, Martin; Landaverde, Mauricio; Sutter, Roland W. (The Journal of infectious diseases, 2010)
Background. As part of an evaluation of strategies to make inactivated poliovirus vaccine (IPV) affordable for developing countries, we conducted a clinical trial of fractional doses of IPV in Cuba. Methods. We compared the immunogenicity and reactogenicity of fractional-dose IPV (0.1 mL, or 1/5 of a full dose) given intradermally using a needle-free jet injector device compared with full doses given intramuscularly. Subjects were randomized at birth to receive IPV at 6, 10, and 14 weeks. Results. A total of 471 subjects were randomized to the 2 study groups, and 364 subjects fulfilled the study requirements. No significant differences at baseline were detected. Thirty days after completing the 3-dose schedule of IPV, 52.9%, 85.0%, and 69.0% of subjects in the fractional-dose IPV arm seroconverted for poliovirus types 1, 2, and 3, respectively, whereas 89.3%, 95.5%, and 98.9% of subjects in the full-dose IPV arm seroconverted for poliovirus types 1, 2, and 3, respectively (all comparisons, P<.001). the median titers of each poliovirus serotype were significantly lower in the intradermal arm than in the intramuscular arm (P<.001). only minor local adverse effects and no moderate or serious adverse events were reported. Conclusions. This large-scale evaluation demonstrates the feasibility of fractional doses of IPV given intradermally as an antigen-sparing strategy but also shows that IPV given to infants at 6, 10, and 14 weeks of age results in suboptimal immunogenicity (especially for the fractional-dose arm). Trial Registration. Controlled-trials.com identifier: ISRCTN19673867.